Pertimbangan Pelanggan dalam Reservasi Hotel Berdasarkan UI/UX Desain Aplikasi - Sani, Yasir; Rizdania Dermawi; Putro, Tegar Wahyu W.W. (Faculty of Social and Political Science, 2025)
Digital transformation in the hospitality industry has increased customer dependence on hotel reservation applications. This study analyzes UI/UX factors influencing customer decisions when choosing a hotel booking application. A quantitative approach was used to survey 284 respondents who actively use hotel reservation applications. Data were analyzed using descriptive statistics and the Structural Equation Modeling (SEM) method to evaluate the relationship between ease of navigation, visual appearance, search features, information transparency, and transaction security on customer satisfaction and loyalty. Results indicate that ease of navigation (78%), visual appearance (82%), search features (85%), information transparency (90%), and transaction security (88%) significantly influence user satisfaction and loyalty. This study extends previous research by highlighting changes in digital behaviour and offering practical recommendations for developers. The findings suggest that users consider information transparency and effective search features the most critical factors. This study provides insight for application developers to continue improving UI/UX to increase customer satisfaction and loyalty in the increasingly competitive digital hospitality industry